2018
DOI: 10.1016/j.jri.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The two-sided role of the vaginal microbiome in Chlamydia trachomatis and Mycoplasma genitalium pathogenesis

Abstract: Sexually transmitted infections (STI) can have major consequences for the reproductive health of women. Mycoplasma genitalium is a STI that is not as well studied but causes pelvic inflammatory disease (PID) among other complications. Another well-known STI is Chlamydia trachomatis, notorious for its capability to cause infertility. Both C. trachomatis and M. genitalium share some of the same clinical aspects. Parts of the pathogenesis of C. trachomatis and M. genitalium infections are unclear but potential fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 59 publications
0
17
0
1
Order By: Relevance
“…The role of the host vaginal microbiota is an understudied factor in the interactions with FSHs and Chlamydia. Studies have suggested that C. trachomatis infection is associated with altered diversity in the vaginal microbiome, as reviewed by Molenaar, et al and others [73,79]. In baboons, C. trachomatis infection in the presence of the LNG-IUS decreased the total number of microbiome-associated bacteria, but not the diversity of the vaginal microbiome [78].…”
Section: Future Directions and Conclusionmentioning
confidence: 94%
“…The role of the host vaginal microbiota is an understudied factor in the interactions with FSHs and Chlamydia. Studies have suggested that C. trachomatis infection is associated with altered diversity in the vaginal microbiome, as reviewed by Molenaar, et al and others [73,79]. In baboons, C. trachomatis infection in the presence of the LNG-IUS decreased the total number of microbiome-associated bacteria, but not the diversity of the vaginal microbiome [78].…”
Section: Future Directions and Conclusionmentioning
confidence: 94%
“…The ability to synthesize tryptophan in the IFNg-rich infection microenvironment is an important virulence factor of the genital C. trachomatis serovars (Aiyar et al, 2014). IFN-g mediates the activation of host indoleamine 2,3-dioxgenase (IDO), leading to the consumption of tryptophan necessary for the growth of C. trachomatis and inhibiting the growth of C. trachomatis (Beatty et al, 1994;Aiyar et al, 2014;Olive and Sassetti, 2016;Molenaar et al, 2018). The tryptophan needed for the growth of C. trachomatis is reduced, and C. trachomatis forms a static state (Byrne et al, 1989).…”
Section: Chlamydia Trachomatismentioning
confidence: 99%
“…After C. trachomatis escapes the host's immunity, the host's immune surveillance is reduced, and the environment is conducive to the growth of C. trachomatis, which is reactivated (Belland et al, 2003). After C. trachomatis reinfection or chronic infection, T helper (Th)1-, Th2-and Th17-type cells are triggered to mediate tissue destruction, fibrosis, and scarring, further leading to the progression of PID and its sequelae (Ziklo et al, 2016a;Molenaar et al, 2018).…”
Section: Chlamydia Trachomatismentioning
confidence: 99%
“…5 Döderlein's bacillus grow in the vagina possess the menstrual cycle and secrete acid, keeping the vagina acidic and repelling the growth of bacteria. [6][7][8] Postmenopausal women lose the environment in which Döderlein's bacillus grow due to reduced hormonal activity. Thus, it has been reported that the vaginal pH increases and the patient becomes susceptible to vaginitis.…”
Section: Introductionmentioning
confidence: 99%